Physics-based modelling of ballistic transport in nanoscale transistor - Saad, Ismail (Institute of Electrical and Electronics Engineers, 2009)
The ballistic transport of the carriers is predicted when the channel length of the transistor is less than the scattering-limited mean-free path. In this paper, the saturation velocity is found to be ballistic regardless of the device dimensions. This saturation velocity is limited by the intrinsic velocity. Its does not sensitively depend on the ballistic or scatteringlimited nature of the mobility. In the degenerate realm, the saturation velocity is shown to be the Fermi velocity that is independent of temperature but strongly dependent on carrier concentration. In the non-degenerate realm, the intrinsic velocity is the thermal velocity that depends only on the ambient temperature. The drain carrier velocity is revealed to be smaller than the saturation velocity due to the presence of a finite electric field. An excellent agreement of the models developed and applied to 80-nm-channel-length MOSFET validates the physics behind ballistic transport.